Corticotropin releasing factor (CRF)-1 receptor antagonist, CP-154,526, blocks the expression of ethanol-induced behavioral sensitization in DBA/2J mice - Fee, Jon R. (2007)
RATIONALE: Manipulation of glucocorticoid receptor signaling has been shown to alter the acquisition and expression of ethanol-induced locomotor sensitization in mice. It is unknown if other components of the hypothalamic-pituitary-adrenal (HPA)-axis modulate locomotor sensitization resulting from repeated ethanol administration. In the present investigation, we determined if pretreatment with an intraperitoneal (i.p.) injection of CP-154,526, a selective corticotropin releasing factor (CRF) type-1 receptor antagonist, would block the acquisition and/or expression of ethanol-induced locomotor sensitization in male DBA/2J mice. METHODS: To assess the role of the CRF(1) receptor in the acquisition of behavioral sensitization, mice were pretreated with an i.p. injection of CP-154,526 30 minutes before each of 10 sensitizing i.p. injections of ethanol. To determine the role of the CRF(1) receptor in modulating the expression of ethanol-induced sensitization, mice that had previously been sensitized to the locomotor stimulant effects of ethanol were pretreated with CP-154,526 30 minutes before an i.p. injection of ethanol on the test day. In a third study, ethanol-naïve mice were pretreated with CP-154,526 30 minutes before an initial i.p. injection of ethanol to determine the combined effects of the CRF(1) receptor antagonist and ethanol on locomotor activity. Blood ethanol concentrations were assessed at the termination of sensitization studies. RESULTS: Pretreatment with CP-154,526 blocked the expression of ethanol-induced locomotor sensitization in DBA/2J mice but did not prevent the acquisition of sensitization. The ability of CP-154,526 to block the expression of ethanol-induced locomotor sensitization was not attributable to alterations in blood ethanol levels or possible sedative effects produced by the combined administration of CP-154,526 and ethanol. CONCLUSIONS: These data provide novel evidence that CRF(1) receptor signaling modulates the expression of ethanol-induced locomotor sensitization, and adds to a growing literature suggesting a role for neurochemicals and hormones associated with the HPA-axis in behavioral sensitization resulting from repeated exposure to drugs of abuse.